2007
DOI: 10.1267/ahc.07024
|View full text |Cite
|
Sign up to set email alerts
|

An Up-to-Date Anti-Cancer Treatment Strategy Focusing on HIF-1.ALPHA. Suppression: Its Application for Refractory Ovarian Cancer

Abstract: AHC Hypoxia inducible factor-1α (HIF-1α) predominantly determines the transcriptional activity of HIF-1, which induces the certain genetic expressions to participate in the proliferation and progression of the tumor. It is supposed that HIF-1α is also an extremely important factor in cancer treatment. Based on the results of our recent analyses using ovarian tumors, which indicated the close association of HIF-1α expression with the acquisition of malignancy and the characterization of histology, we further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Together with the fact that ovarian cancers have been reported to overexpress HIF-1α and HIF-1 protein-coding target genes, it was plausible to predict that ovarian cancers would also overexpress miR-210 as a potential oncogene. 35,36 The opposite, however, turned out to be true. Ovarian cancers demonstrate deletions and reduced expression of miR-210 when compared to healthy donors, evidence that supports a tumor suppressor role for miR-210.…”
Section: Hypoxic Regulation Of Mir-210mentioning
confidence: 94%
“…Together with the fact that ovarian cancers have been reported to overexpress HIF-1α and HIF-1 protein-coding target genes, it was plausible to predict that ovarian cancers would also overexpress miR-210 as a potential oncogene. 35,36 The opposite, however, turned out to be true. Ovarian cancers demonstrate deletions and reduced expression of miR-210 when compared to healthy donors, evidence that supports a tumor suppressor role for miR-210.…”
Section: Hypoxic Regulation Of Mir-210mentioning
confidence: 94%
“…16 Because it promotes malignant transformation and development of histological tumor characteristics 7 including angiogenesis, 16 inhibition of Glut-1 is currently being evaluated as a therapeutic strategy. 15,17 Cantuaria et al studied the IHC expression of Glut-1 in 113 primary ovarian carcinomas. 18 Glut-1 was more frequently expressed in the poorly differentiated tumors compared with the more differentiated counterparts.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofmentioning
confidence: 99%
“…13,16,17 In our studies so far, HIF-1a expression profiles differed to some extent depending on the histological type of the ovarian carcinoma, 20,21 and the decrease in expression of HIF-1a and VEGF was demonstrated in the rapamycin-treated cell line from refractory CLA. 22 These results motivated us to clarify the status of HIF-1a-related factors in ovarian carcinomas and explore the clinicopathological significance of HIF-1a inhibition from the point view of anti-cancer therapy. In the present study using surgical specimens, CLA was found to be characterized by overexpression of HIF-1a in the nucleus and also aberrant activation of the mTOR signaling pathway, compared to SEA.…”
mentioning
confidence: 99%